(untitled) (Revista de Psicología, 2025)
In Mexico, violence against women is a phenomenon that has been steadily increasing. Contrary to what might be expected from the cultural evolution of societies in a more egalitarian direction and the advance of feminist movements, it is young women who are at the greatest risk of suffering gender violence. The purpose of this qualitative study was to investigate the Social Representations that three generational groups construct about the violence against women. A sample of 500 young people (n = 170), adults (n = 167) and elders (n = 163) who were administered a free word association questionnaire participated in this study. The results showed that there is a dichotomy in the representations elaborated. On the one hand, each generational group elaborated its own type of representation. The group of elders constructed a Social Representation centered on traditional stereotypes of women that revolves around cultural and traditional values. The adult group constructed a Social Representation centered on gender roles and social norms. The younger focused their Social Representation on sexist attitudes and behaviors built from their mediated experiences of violence. However, there were also consensual representations among the three groups that attributed the causes of violence against women to structural, cultural and social factors.